(untitled) (Al-Academy, 2023)
Contemporary arts have achieved, in accordance with the transition of concepts, a new logic in presentation and expression in general, and specifically in the field of ceramic art. The shift towards the logic of rejection and subversion of prevailing methods, which have been almost a constant foundation for a long period, has directly influenced the direction of visual arts in the contemporary world. The growth and cultural transformations that the world has witnessed after the two World Wars have produced cognitive shifts based on strategies that diverge from the dominant culture. These approaches vary according to existential needs, as the language of art has become conceptual and a medium for contemporary culture with its rapid and expanding rhythm. Thus, contemporary ceramic art has encompassed a diverse range of concepts expressing a specific philosophy tied to technology and scientific progress as means that directly contribute to the development of aesthetic values and artistic formations in alignment with the culture of the era. The concepts of this art form have changed and transformed in terms of presentation style and formal outcome .There is no longer a specific definition for fixed techniques and materials. Instead, we find that contemporary potters have moved beyond the boundaries of their traditional artistic field, under the concept of assemblage , achieving a form that is not subject to homogeneity .They employ renewed presentation methods that are not limited to enclosed spaces but are open in their settings, creating a visual witness in which the artist and the recipient participate in the idea and interpretation , fostering a dialectical and intellectual discourse linked to issues subject to discussion within the inevitability of existence.